Meningkatkan Hasil Belajar dan Berfikir Kritis PAKBP dengan Model PBL Berbantuan Media Audio Visual Fase B Kelas IV SDN Sawahan - Albertin Noviyantiningtyas; FR. Wuriningsih; Budi Hartana (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2024)
The implementation of the "Merdeka Belajar" (Freedom to Learn) Curriculum faces various challenges, including in terms of curriculum implementation and adjustment. These challenges include changes in student learning patterns, the broader role of teachers, and efforts to meet the established educational standards. In the context of the Merdeka Curriculum, Catholic religious education in Indonesia focuses on developing students' understanding of religion, moral values, and Catholic spirituality, while also emphasizing the Pancasila student profile.The Merdeka Curriculum has also had impacts and posed challenges at SD Negeri Sawahan Surakarta regarding students' academic performance or learning outcomes. For example, in the cognitive aspect, when studying the Grade IV lesson on Developing My Abilities, the students' learning outcomes were unsatisfactory. Out of a total of 6 students, around 4 (67%) scored below the Minimum Completeness Criteria (KKM), which was set at 75. In this classroom action research, the researcher focuses on the dimension of critical thinking, based on the importance of building strong character and mental attitudes in the younger generation, especially in facing complex global challenges. Creative thinking skills will result in more effective learning and develop higher reasoning abilities that can be used to solve various problems in learning. Students with creative thinking skills tend to have high intrinsic motivation, strong drive, self-confidence, and better thinking abilities. In this model, the teacher acts as a facilitator who helps students develop deep understanding and relevant skills through motivation, stimulating questions, and support for meaningful learning experiences. PBL focuses on common everyday problems, and its process involves problem identification, data collection, and the use of data to solve problems. The primary goal of PBL is to develop critical thinking, problem-solving skills, and knowledge acquisition, helping to improve students' learning outcomes and critical thinking skills in the topic of developing self-abilities in Grade IV at SD Negeri Sawahan, Surakarta.